English as a foreign language pre-reading skills readiness at Kindergarten level - Gross Morillo, María Alejandra (2012)
This study examined varied methodologies available for the development of pre-reading skills, making an emphasis on phonics and how it may affect reading fluency. A Kindergarten student was evaluated on her knowledge of phonics, phonemic awareness and phoneme isolation during a period of 28 weeks. Information was gathered from in-class observation as well as from analyzing student work, and using oral and written evaluations. The researcher predicted that using varied methodologies together, over a single approach enhances the early pre-reading process which is consistent with the opinions of Bramberger (as cited in Corporación Futuro, 2012). By itself, phonics instruction presented advantages as well as disadvantages which will only become more apparent once the student reaches reading age. Additionally, it was examined how the knowledge that teachers have of the TESOL/NCATE standards may have an impact on the development of their students. Overall, the researcher recommends for phonics instruction not be thought of as a standalone approach when preparing students to read, relying on the TESOL/NCATE standards as a guide.